2021
DOI: 10.1007/s00402-021-04200-8
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of the medial collateral ligament of the knee: a systematic review

Abstract: Introduction The primary aim of this investigation was to systematically review relevant literature of various imaging modalities (magnetic resonance imaging (MRI), stress radiography and ultrasonography) in the assessment of patients with a medial collateral ligament (MCL) injury. Materials and methods A systematic literature review of articles indexed in PubMed and Cochrane library was performed. Original research reporting data associated with medial ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Study by Meyer et al found that interestingly, preoperative clinical examination was slightly inferior to stress radiography in the detection of MCL lesions. 6 However, clinical testing under general anaesthesia performed similar to stress radiography. The methodological quality analysis showed a low risk of bias regarding patient selection and index testing in each imaging modality.…”
Section: Discussionmentioning
confidence: 99%
“…Study by Meyer et al found that interestingly, preoperative clinical examination was slightly inferior to stress radiography in the detection of MCL lesions. 6 However, clinical testing under general anaesthesia performed similar to stress radiography. The methodological quality analysis showed a low risk of bias regarding patient selection and index testing in each imaging modality.…”
Section: Discussionmentioning
confidence: 99%
“…This increased widening of the medial knee joint gap has been found in studies using x-ray and ultrasound imaging techniques. 5,14 The results of the cadaver and finite element studies suggest that injury of the dMCL or POL structures should result in greater widening of the medial joint gap during the ANTMED rotational stress test. 7,[15][16][17] Improved understanding of the clinical tests for the assessment of knee ANTMED rotational stability will lead to earlier recognition of injury to the dMCL and POL and will likely lead to improved outcomes for patients with ANTMED rotational knee instability.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, the accuracy of this test in quantifying MCL injuries is highly susceptible to the examiner's subjective interpretation and has proven to be unreliable, especially in an acute setting. 15 Diagnostic confirmation has thus often relied on provocative stress maneuvers under imaging. 15,16 The current gold standard modality for evaluating medial knee injury is magnetic resonance imaging (MRI); however, because medial knee instability is a dynamic process, assessing the appearance of the medial knee ligaments on static MRI can result in high false-negative rates.…”
mentioning
confidence: 99%
“…15 Diagnostic confirmation has thus often relied on provocative stress maneuvers under imaging. 15,16 The current gold standard modality for evaluating medial knee injury is magnetic resonance imaging (MRI); however, because medial knee instability is a dynamic process, assessing the appearance of the medial knee ligaments on static MRI can result in high false-negative rates. 8,15 Furthermore, it does not allow for a comparison with the contralateral healthy side.…”
mentioning
confidence: 99%
See 1 more Smart Citation